Self-management of persons living with diabetes mellitus type 2: Experiences of diabetes nurse educators - Coleen O'Brien; Dalena van Rooyen; Esmeralda Ricks (AOSIS, 2020)
Background: The global pandemic of diabetes mellitus type 2 (DM2) is the direct cause of significant health and economic problems for both governments and individuals owing to the high level of morbidity and mortality. South Africa has the second highest incidence of DM2 in sub-Saharan Africa. Aim: This article describes the experiences of diabetes nurse educators in relation to self-management of DM2 of persons living with DM2. Setting: This article involves nurse educators working in diabetes clinics in public and private hospitals in Nelson Mandela Bay Municipality, South Africa. Methods: A semi-structured interview guide was used to collect data from a focus group interview comprising three participants and two individual interviews. The interviews were recorded with the permission of participants, transcribed and then coded using Tesch's model of data analysis. Themes were agreed upon with the consensus of the researcher, two supervisors and an independent coder. Results: Three themes were identified: (1) diabetes nurse educators have clear perceptions about the importance of self-management of DM2 of persons living with DM2, (2) there are factors that affect persons living with DM2 with respect to self-management and (3) there are ways in which professional nurses can assist persons living with DM2 in the self-management of their condition. Conclusion: This article identified factors that diabetes nurse educators experienced in either assisting or hindering patients in self-management of their DM2. The diabetes nurse educators voiced their views on how professional nurses can provide support to the patients living with DM2.